Characterization of the enzymatic activity and physiological function of the lipid droplet‐associated triacylglycerol lipase AtOBL1. Issue 3 (27th November 2017) - Müller, Anna Ophelia; Ischebeck, Till
Summary: Similar to seeds, pollen tubes contain lipid droplets that store triacylglycerol (TAG), but the fate of this TAG as well as the enzymes involved in its breakdown are unknown. Therefore, two potential TAG lipases from tobacco and Arabidopsis, NtOBL1 (Oil body lipase 1) and AtOBL1, were investigated, especially with respect to their importance for pollen tube growth. We expressed NtOBL1 and AtOBL1 as fluorescent fusion proteins to study their localization by confocal microscopy. Furthermore, we overexpressed AtOBL1 in Nicotiana benthamiana leaves to characterize it enzymatically. The obl1 mutant was studied in respect to its pollen tube growth in vivo and its seed germination. Both NtOBL1 and AtOBL1 localized to lipid droplets. AtOBL1 was abundant in pollen tubes and seedlings, and acted as a lipase on TAG, diacylglycerol and 1‐monoacylglycerol at a pH optimum of 5.5. The obl1 mutant was hampered in pollen tube growth, whereas seedling establishment was not affected under optimal conditions, even though AtOBL1 accounted for a major lipase activity in seeds. TAG could be a direct precursor for the synthesis of membrane lipids in pollen tubes and proteins of the OBL family involved in the flux of acyl groups.